Estimating the effects of financial inclusion on welfare in sub-Saharan Africa - Grace Ofori-Abebrese; Samuel Tawiah Baidoo; Ebenezer Essiam (Cogent Business & Management, 2020)
The prominent role of financial inclusion in every economy-as it has been widely acknowledged as an enabler to achieving eight out of the 17 Sustainable Development Goals (SDGs) cannot be overemphasized as far as the welfare of individuals is concerned. This study estimates the effects of financial inclusion on welfare using cross-section data from 33 sub-Saharan African countries and the ordinary least squares technique is employed for the analysis. The results from the financial inclusion index estimation reveal that, generally, financial inclusion in the sub-region is low as 29 out of the 33 sampled countries have low financial inclusion index. It is also revealed that financial inclusion has positive effect on welfare. With regard to the control variables, the study reveals that education and income also improve welfare. Based on the positive effect of financial inclusion on welfare, important implications that seek to promote financial inclusion in the sub-region have been provided for policy consideration.
Keywords: G10; G20; I30; I31; 650; Financial inclusion; financial system; welfare; sustainable development goals; sub-Saharan Africa; Africa